USING THE QUIZLET APPLICATION IN IMPROVING STUDENTS’ ENGLISH VOCABULARY AT SMP TUJUH LIMA MAKASSAR - Varian, Devlin Janitra; Muliati, Muliati; Rampeng, Rampeng (THE ACADEMIC: ENGLISH LANGUAGE LEARNING JOURNAL, 2025)
This research aims to determine the improvement in students' English vocabulary using the Quizlet application on seventh grade at SMP Tujuh Lima Makasssar academic year 2024/2025. This research used a pre-experimental method with a one-group pre-test and post-test design. The research samples were from 22 seventh-grade students at SMP Tujuh Lima Makassar. Data were collected through a multiple-choice vocabulary test administered before and after the treatment. During the treatment, students learned vocabulary through various features in the Quizlet application, which made learning more interesting. Data were analyzed using descriptive statistics and paired t-test using SPSS version 25. The results of this research indicate that students' vocabulary scores improved significantly after using Quizlet. The average score increased from 54.45 on the pre-test to 73.23 on the post-test. The paired t-test results showed a significance level of 0.000 < 0.05, indicating that the improvement was statistically significant. Additionally, through Quizlet's interactive features, students became enthusiastic, active, and motivated in vocabulary learning, enabling the Quizlet application to improve students' English vocabulary mastery.